Participação do óxido nítrico na fisiopatologia da doença renal crônica - Baptista Galvão, André Luiz (2014)
Nitric oxide (NO) is a free radical gas, inorganic, which has seven electrons of nitrogen and oxygen eight, possessing an unpaired electron. This radical is produced from L-arginine by a reaction mediated by the enzyme NO synthase. NO it is about a radical of who acts abundant on a variety of biological processes, particularly when produced by endothelial cells plays a significant role in cardiovascular control, as a modulator of peripheral vascular resistance and platelet aggregation. This free radical has also a neurotransmitter and mediator of the immune system. NO kidney function has been considered in many physiological functions such as: (a) regulation of hemodynamics and glomerular function tubuloglomerular, (b) participation in pressure natriuresis (c) maintaining medullar perfusion (d) inhibiting sodium reabsorption tubular, and (e) acting as a modulator of the activity of the sympathetic nervous system. Given these functions, the occurrence of its deficiency is associated with chronic kidney disease (CKD) in vasoconstriction and consequently glomerular hypertension, high blood pressure (HBP), proteinuria and progression of renal dysfunction. This work has the scope to describe the role of NO in renal physiology and pathophysiology of CKD.